Hak Asasi Manusia Islam dan Barat: Studi Kritik Hukum Pidana Islam dan Hukuman Mati - Habib Shulton Asnawi (UIN Sunan Kalijaga Yogyakarta, 2012)
In the human, there is a universal and binding standards. Thus, the principle of respect (to respect), protection (to protect) and fulfillment (to fulfill) Human Rights describes as